Analysis of the Application of Lean Construction Methods in a Number of Contractors in West Java Region - Firdaus, Nanda Ridho; Hidayat, Nur Muhammad Syarif; Gumilar, Muhammad Agung; Rozy, Niko (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to explore the application of Lean Construction methods to reduce waste in construction projects in West Java. Inefficiencies often arise from seven types of waste: waiting, inventory, motion, overproduction, inappropriate processing, transportation, and defects. Data were collected through a quantitative approach, by distributing questionnaires to construction experts in the West Java region. Data analysis utilized a Likert Scale to determine the intensity level of each waste category. From 14 respondents, the two highest waste categories were Waiting (weather disturbances) and Transportation (the distance of suppliers to the project site). Root cause analysis was conducted using the 5 Why method with experienced respondents. The main issues identified were poor planning, inefficient logistics, and improper supplier selection.